Resistivity structural imaging of the Olkaria Domes geothermal field in Kenya using 2D and 3D MT Data inversion. (July 2022) - Omollo, Philip; Nishijima, Jun; Fujimitsu, Yasuhiro; Sawayama, Kazuki
Highlights: Low resistivity at a depth around the ring structure is due to hydrothermal activities related to magma emplacement and partial melt. The resistivity models in Olkaria revealed three layers varying with increasing depth. The dimensionality analysis revealed a near subsurface zone composed mainly of 1D and 2D structures while the 3D structures dominate the deeper part of the reservoir. A relatively high resistive zone beneath the caprock infers permeable pathways associated with upwelling magmatic fluid circulation ABSTRACT: The 2D and 3D MT inversion from 290 soundings were analyzed to visualize the nature and extent of structural control of the Olkaria geothermal reservoir system within and outside the ring structure. The ring structure bounds the drilled geothermal field under exploitation to the east and south of Olkaria Domes. The nature of subsurface structures was classified using dimensionality analysis. The resistivity models revealed three layers varying with depth. The upper conductive layer immediately below the surface as the reservoir seal, underlain by a resistive reservoir zone at about 2.5 − 4 k m, and the deeper conductive zone at a depth of about 5.5 − 8 k m interpreted as the heat source. The resistivity structure forming a channel to the near surface, is interpreted as the hydrothermal fluid's fault pathway. The study also shows the structures resembling sill formations mapped outside the geothermal system in the Domes field, while the dykes predominate in the reservoir.